Ocena możliwości ko-fermentacji osadów koksowniczych i komunalnych = Evaluation of the possibility of co-fermentation coke sludge and municipal sludge - Macherzyński, Bartłomiej; Włodarczyk-Makuła, Maria; Turek, Agnieszka; Nowacka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents results of research on changes in the physicochemical properties during co-fermentation process of coke and municipal sludges. The process was carried out at 37°C for 20 days, for the three mixtures of sludge. The mixture of raw sludge and excessive sludge inoculated with fermented sludge was a control sample.
Keywords: kofermentacja; komunalne osady ściekowe; osady koksownicze; biogaz; co-fermentation; sewage sludge; coke sludge; biogas